PENGARUH SUPERVISI KEPALA SEKOLAH DAN LINGKUNGAN KERJA TERHADAP PROFESIONALISME GURU DAN KINERJA GURU SMP NEGERI 1 GONDANG BOJONEGORO - Purbawati Handayani; Indra Prasetyo; Ruddy Wiroko (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2018)
The study was conducted to determine the effect of teachers on teacher performance in SMPN 1 Gondang, Bojonegoro. The population in this study is all teachers of SMP Negeri 1 Gondang living 31 people. The sample in this study using different sampling census with the leader, the entire population was sampled as many as 30 people. Data processing is done using path analysis. Path analysis method is multiple linear regression which is used to estimate the causality relationship between variables in research model built on strong theory. The results of the analysis show that the principal, work environment and professionalism of teachers are partially insignificant to the performance of teachers SMP Negeri 1 Gondang. The principal academic supervision, work environment and professionalism of teachers are simultaneously significant to the performance of teachers of SMP Negeri 1 Gondang. Among the academic supervision of school principals and the environment there is no dominant effect on teacher performance through teacher professionalism. Keywords: principal supervision, work environment, teacher professionalism, teacher performance